2020
DOI: 10.1101/2020.07.24.20161828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 automated diagnosis and risk assessment through Metabolomics and Machine-Learning

Abstract: COVID-19 is still placing a heavy health and financial burden worldwide. Impairments in patient screening and risk management play a fundamental role on how governments and authorities are directing resources, planning reopening, as well as sanitary countermeasures, especially in regions where poverty is a major component in the equation. An efficient diagnostic method must be highly accurate, while having a cost-effective profile. We combined a machine learning-based algorithm with instrumental analysis usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…In our study, we compared the lung and systemic responses in association with the lung transcriptome and demonstrated a robust correlation between lipid mediators, neurotransmitters, and their receptors in SARS-CoV-2 infection. However, contrary to what has been suggested by previous studies 37, 38 , only small amounts of eicosanoids were found in the plasma of patients with severe/critical disease, with significant differences observed only in AA, 5-HETE, and 11-HETE. Interestingly, the levels of 5-HETE and 11-HETE were found to be remarkably higher in BAL, as well as AA in plasma, suggesting that AA and its metabolites mediate responses to Covid-19.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we compared the lung and systemic responses in association with the lung transcriptome and demonstrated a robust correlation between lipid mediators, neurotransmitters, and their receptors in SARS-CoV-2 infection. However, contrary to what has been suggested by previous studies 37, 38 , only small amounts of eicosanoids were found in the plasma of patients with severe/critical disease, with significant differences observed only in AA, 5-HETE, and 11-HETE. Interestingly, the levels of 5-HETE and 11-HETE were found to be remarkably higher in BAL, as well as AA in plasma, suggesting that AA and its metabolites mediate responses to Covid-19.…”
Section: Discussioncontrasting
confidence: 99%
“…First, mass spectrometric data is preprocessed for ion annotation (intensity, width, resolution, and m / z ), alignment, normalization, and denoising. 17 Three partitions of data are segregated according to the best practices of ML, consisting of fitting (training and validation), test, and blind test partitions. The final classification results are reported using the blind test (see Figure 2 a).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.analchem.0c04497 . Detailed data preprocessing and ML modeling method; Tables with model validation with several algorithms, multiclass confusion matrix, and biomarkers elucidation data through mass spectrometry; Preprocessed mass spectrometry 17 data available at: ; Deidentified patient information will be made available from corresponding author upon request ( PDF ) …”
mentioning
confidence: 99%
“…Powered by the growing applications of high-resolution mass spectrometry (MS), metabolomics has become a key member of the omics toolkit in biomedical research. Multiple metabolomics studies have been recently conducted across the world to study COVID-19, revealing key metabolic dysregulations during the disease’s progression [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For instance, several amino acids have been observed to be positively correlated with the severity of COVID-19 as key indicators of clinical prognosis of the disease [ 8 , 9 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%